The reactivity of desmosterol and other shellfish- and xanthomatosis-associated sterols in the macrophage sterol esterification reaction. - Tabas, I (1989)
The acyl-CoA: cholesterol acyl transferase (ACAT) reaction in macrophages is a critical step in atherosclerotic foam cell formation, but little is known about the reaction's sterol substrate specificity. In this report we examine the macrophage ACAT reactivity of the shellfish sterol, desmosterol, and other sterols found in man because of shellfish ingestion or in association with the foam cell diseases sitosterolemia and cerebrotendinous xanthomatosis (CTX). We first show that the J774 macrophage, a foam cell model with a hyperactive ACAT pathway, synthesizes desmosterol instead of cholesterol and that both endogenous and exogenous desmosterol are substrates and stimulators of the ACAT reaction in these cells. When exogenous desmosterol was added to human monocyte-derived macrophages, ACAT was stimulated 29- and 4-fold compared with control and cholesterol-treated cells, respectively. Steryl ester mass accumulation in desmosterol-treated human macrophages was 10-fold greater than in control cells and 3-fold greater than in cholesterol-treated cells. Another shellfish sterol, 24-methylene cholesterol, also stimulated ACAT in human macrophages, but most of the xanthomatosis-related sterols did not stimulate ACAT. These data suggest that: (a) the shellfish sterols desmosterol and 24-methylene cholesterol may be atherogenic; and (b) the excessive foam cell formation seen in sitosterolemia and CTX cannot be explained by ACAT hyperreactivity of their associated sterols.